2020
DOI: 10.1007/s10750-020-04467-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus control on primary productivity and deep-water oxygenation: insights from Lake Lugano (Switzerland and Italy)

Abstract: Attempts to restore Lake Lugano, Switzerland and Italy, from eutrophication have produced weak responses in the target variables (primary productivity and hypolimnetic oxygen concentrations), indicating shortcomings in the underlying eutrophication model. An analysis of monitoring data showed that the decrease in phosphorus concentration, although nearly compliant with restoration targets, produced only slight decreases in primary productivity and no change in hypolimnetic oxygen conditions. These target varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Similar effects have been described for the deep subalpine lakes Garda (Salmaso et al, 2018) and Lugano (Lepori et al, 2018) as well for other deep lakes North of the Alps (Yankova et al, 2017;Schwefel et al, 2019). These results overall are extremely important for water quality objectives: restoration targets should be revised taking into account the influence of climate-related drivers such as mixing depth and stability (Lepori and Capelli, 2021).…”
Section: External and Internal Drivers Of The Long-term Evolution Of Nutrients Concentrationssupporting
confidence: 75%
“…Similar effects have been described for the deep subalpine lakes Garda (Salmaso et al, 2018) and Lugano (Lepori et al, 2018) as well for other deep lakes North of the Alps (Yankova et al, 2017;Schwefel et al, 2019). These results overall are extremely important for water quality objectives: restoration targets should be revised taking into account the influence of climate-related drivers such as mixing depth and stability (Lepori and Capelli, 2021).…”
Section: External and Internal Drivers Of The Long-term Evolution Of Nutrients Concentrationssupporting
confidence: 75%
“…We addressed these questions by analysing time series of monitoring data (question 1) and using a predictive modelling approach (questions 2 and 3). The time-series analysis summarizes and updates previously-published work (Lepori, 2019a;Lepori and Capelli, 2021). The predictive modelling is new.…”
Section: Articlementioning
confidence: 73%
“…An explanation for the model tendency to overestimate the observed values in this study is that the initial oxygen concentration (HO LW ) in Lake Lugano probably differed from those of the calibration set [Müller et al (2019) mention 10 mg L -1 as a typical HO LW value, whereas we observed average values of 5-6 mg L -1 ]. This difference would bias the predictions because, in deep Alpine lakes, AHOD tends to be positively associated with HO LW (higher HO LW results in faster hypolimnetic oxygen depletion; Rogora et al, 2018, Lepori andCapelli, 2021). Therefore, in Lake Lugano, lower HO LW values could have caused lower AHOD values relative to lakes in the calibration set with similar phosphorus concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus reduction can also reduce the frequency and severity of harmful algal blooms and sustain the habitat for fish and other species that are sensitive to hypoxia. Various mitigation measures have successfully reduced P loads, , but the effects of P reduction on primary production tend to show little change in deep-water O 2 consumption during the early phases of recovery from eutrophication. Changes in primary production and subsequent hypolimnetic O 2 consumption may become evident only at TP concentrations significantly lower than those previously expected . Oxidation of sediment layers and their reduced substances may limit improvements in hypolimnetic O 2 concentrations. , Furthermore, primary production in lakes varies seasonally and interannually, and the detection of trends in the rates of production typically depends on the long-term monitoring data.…”
Section: Introductionmentioning
confidence: 99%